APPLICATION OF THE SERVQUAL METHOD TO MEASURE STUDENT SATISFACTION - M. Yusuf; Hambali; Akmal (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Student satisfaction services for SMA Negeri 3 Tanjungbalai have not been analyzed yet. So that the impact is less than optimal satisfaction services for facilities at SMA Negeri 3 Tanjungbalai, inadequate training of teaching staff, administrative services. By looking at these conditions, it becomes the impetus for making a decision-making system regarding participant satisfaction services using an information systems technology approach. Based on these problems, it is important to conduct research related to the assessment of service quality at SMA Negeri 3 Tanjungbalai to find out how the quality of services provided to especially trainers and become an evaluation for SMA Negeri 3 Tanjungbalai to improve services.